Digital Economy in the Context of Phylogenesis of Innovation and Market Development - Stroev, P.V.; Firsov, D.V.; Reshetnikov, S.B. (Journal of Reviews on Global Economics, 2019)
Understanding the phylogenetic origin of a concept of innovation stands as the main precipice in establishing a sustainable concept of innovation. And as a scientific direction in studying emergence, distribution and commercialization of innovations. Primary Novelty of present article is expressed through analysis of neoindustrialization as a process of transition to a new economic paradigm through renewal of industrial infrastructure and its form of organization in a Technetronic phase of development. Comparative, comprehensive and factor analysis stands as the main methodology for the present article. Primary data consists of government and commercial statistics. The empirical analysis shows the importance of the vertically integrated structures in the course of new cluster development as well as their weight and importance in the development of the modern digital economy. Results of a research of Economist Intelligence Unit in 82 countries of the world say that such countries as Mexico or China, quickly improve the skills in the field of innovations. The research allowed being elicited one remarkable fact: the countries with the average level of economic welfare have additional benefits that introduction of domestic innovative developments stimulates also faster development of foreign experience.